Spatial and Temporal Changes of Technology: Implications of IT on Promoting On-Job Training in Faith Based Organizations in Ugandan Context - Kiwanuka, Fred (European Journal of Applied Sciences, 2026)
Integrating information technology into on-job training programs can enhance learning outcomes. Emerging technologies are revolutionizing how FBOs approach professional training. Therefore, the study aimed at establishing the implications of IT on promoting on-job training in Faith Based Organizations in Ugandan Context. The study objectives included: to identify the emerging online training platforms for employees among FBOs, to explore the implications thereof for on-job training among FBOs, to analysis the challenges encountered by FBOs in handling on-job training, to assess how best do the FBOs in Uganda perceive and address IT advancement concerns, and to establish what can be employed by the FBOs as an alternative model in addressing obstacles in online job training and skilling. The study was based on a qualitative ethnographic research design. Purposive sampling was used in selecting top management and employees (operational staff). The sample size was guided by the principle of data saturation. Interviews focus group discussions, documentary checklist and participant observation was used providing adequate data, while analyzed basing on thematic, content and narrative analysis. The study revealed that the use of IT in promoting on-job training is a critical aspect of modern organizational development, enabling workers to adapt to technological changes, enhance their skills and abilities, and drive innovation within the FBOs. IT enhance on-job training has a positive impact on on-job training efficiency, effectiveness and employee development. It further allows for the integration of digital resources towards supplementing traditional training methods, leading to improved learning outcomes. It also concluded that IT enables the encoding of subject knowledge and teaching skills into software, allowing for personalized and innovative on-job training approaches. The study concluded that key barriers and challenges of IT includes, unqualified IT employees, data security concerns, poor computer literacy, limited computer access, lack of trust in computer applications, lack of training availability, limited technical support, and inadequate technical support in the adoption of EMR systems. The study concluded that information technology has an implication on promoting on-job training in Faith Based Organizations in Uganda. The study recommends that to effectively utilize IT in promoting on-job training, FBOs organizations can consider several practical interventions based on research findings. Future research should focus on exploring emerging technologies such as virtual reality, artificial intelligence, and augmented reality in promoting on-job training.